Pharmacist's work in primary health care for municipalities in southern Brazil - Priscila S. OLIVEIRA; Diogo PILGER; Vera L. MARTINS; Denise BUENO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objectives: The objective of this study is to analyze the work of pharmaceutical pharmacists working in primary health care in municipalities in the state of Rio Grande do Sul. Methods: The study included the 18 municipalities that host the Regional Health Coordination of the Health Secretariat of the State of Rio Grande do Sul and municipalities, with more than 100 thousand inhabitants, totaling 30 municipalities. Data collection was used an electronic questionnaire distributed from March to May 2021 through electronic means. Results: We obtained 77 respondents with a mean age of 39.9 years, prevalence of white color and women. Of all participants, 58 (86.6%) had a post-graduation in Lato Sensu. In professional practice, 33 (42.9%) were pharmacists in charge of the technical and 12 (15.5%) worked in more than one function in the municipality. Regarding the working day, an average working day of 35.3 hours per week was observed. Conclusion: Asymmetry in the distribution of the pharmacist's workforce and work in more than one function stands out. This study can help the management of pharmaceutical care in the organization and ensure the quality of the services provided, and it is suggested studies that evaluate the intensity of work of pharmacists.